2021
DOI: 10.1007/s00300-021-02870-z
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater early life growth influences partial migration in populations of Dolly Varden (Salvelinus malma malma)

Abstract: Populations of northern Dolly Varden (Salvelinus malma malma) exhibit partial seaward migration, yet little is known about this phenomenon in Dolly Varden populations. Our study analyzed data from three different Dolly Varden populations in the western Canadian Arctic in order to determine if: (1) differences in size-at-first seaward migration exist between fish that migrate at early and late ages among populations inhabiting different river systems, and (2) annual growth influences anadromous or resident life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…These length and age values are comparable to those for conspecifics at similar latitudes (Maekawa and Nakano, 2002), although older individuals occur in Arctic populations (Stolarski and Sutton, 2013;Gallagher et al, 2016). Morrison et al (2021) reported that rapid growth in fresh water was associated with early age at first migration in Dolly Varden and that growth rate in fresh water is typically inversely related to smolt age in salmonids (McCormick et al, 1998;. In contrast to the modest differences in size and age between the populations on opposite sides of Bristol Bay, a clear difference in age at migration was observed.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…These length and age values are comparable to those for conspecifics at similar latitudes (Maekawa and Nakano, 2002), although older individuals occur in Arctic populations (Stolarski and Sutton, 2013;Gallagher et al, 2016). Morrison et al (2021) reported that rapid growth in fresh water was associated with early age at first migration in Dolly Varden and that growth rate in fresh water is typically inversely related to smolt age in salmonids (McCormick et al, 1998;. In contrast to the modest differences in size and age between the populations on opposite sides of Bristol Bay, a clear difference in age at migration was observed.…”
Section: Resultssupporting
confidence: 71%
“…Similarly, a population of the southern subspecies of Dolly Varden along the southern Alaska Peninsula also migrated to sea at a younger age, although at a smaller body size at that age of migration . Dolly Varden at the northern end of their range also smolt at a younger age than the fish sampled from the Nushagak District ( Morrison et al, 2021).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, numerous studies have demonstrated the importance of juvenile growth rate on migration propensity (e.g. Kraus & Secor, 2004; Morrison et al., 2021), or how migration can itself lead to increased juvenile growth (Barrow et al., 2021). In some scenarios, growth rate and/or larger body size is positively correlated with migration probability, which is generally assumed to reflect a threshold size which must be attained by individuals to meet energetic demands necessary for migration (Chapman et al., 2012).…”
Section: Introductionmentioning
confidence: 99%